Intervention of Emergency Northern Recovery Project (ENReP) Project in Conflict Affected Northern Sri Lanka - Sivakumar, S. (The International Journal Research Publications, 2013)
Emergency Northern Recovery Project (ENReP) was prepared in a rapidly changing environment. The project preparation was initiated in July 2009, when there were over 290,000 people held in 2 camps. It was initiated to allow these people to return home and have freedom of movement. After that the situation has changed dramatically with approximately 140,000 people were released from camps. Moreover, the Government announced on November 23, 2009, that all movement restrictions both in and out of the camps. Consequently, the immediate challenge has now shifted from moving the people out of the camps to putting in place arrangements to help the returnees to restore their livelihoods and get access to minimal levels of services in their communities.Emergency Northern Recovery Project (ENReP) under the Ministry of Economic Development is supporting the rapidly settling IDPs in the Northern Province to resettle in their place of origin to start their livelihood through; Emergency assistance to IDPs, workfare programme (cash for work), Rehabilitation and reconstruction of essential public and economic infrastructure covering the 5 districts (Vavuniya, Mannar, Kilinochchi, Mullaitivu and Jaffna
Keywords: Rehabilitation; reconstruction